PENGEMBANGAN GAME EDUKATIF BERBASIS SMART APPS CREATOR DALAM MENINGKATKAN LITERASI KESEHATAN ANAK - Roby Naufal Arzaqi; Karunia Rahayu, Aisah (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2025)
Early childhood health literacy is an important skill that supports the formation of healthy living habits from an early age. However, health literacy learning is often less attractive to children because it is delivered passively. This research aims to develop a prototype of an interactive educational Game specifically designed to improve early childhood health literacy. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation (Branch, 2009). This study focuses on the Development stage, which includes a needs analysis through interviews with three early childhood education teachers, one pediatrician (as early childhood and health literacy expert), and one IT specialist (as game prototype development expert). The results of the study show that relevant health literacy themes include personal hygiene, healthy diet, and physical activity. The Game prototype